Analisis Signifikansi Perkembangan Emosional dan Perilaku Anak dengan Pengasuhan Orangtua melalui Strength and Difficulties Questionnaire (SDQ) - Nurhayati (Jurnal Tinta, 2025)
Based on the reflective thought on how children’s hyper emotional responding to an action that requires attention and patience in RA Shodrul Ulum Brongkal, this research aims to identify concrete relation between children’s emotional development and behavior with certain kind of parenting. This research conducted towards 58 respondents parents in RA Shodrul Ulum Brongkal. Research methods in this study uses quantitative SDQ (Strength and Difficult Questionnaire) for collecting data and uses SPSS program to analyze the data. This research shows that student’s emotional and behavior development significantly related to parenting model. Extreme behavior and hyper reactive emotions also consider as the result of how parents-child relationship and communication.